Supplementation of postbiotic RI11 improves antioxidant enzymes activity, upregulated gut barrier genes and reduced cytokine, acute phase proteins and heat shock protein70 gene expression levels in heat-stressed broilers - Humam, Ali Merzza; Loh, Teck Chwen; Foo, Hooi Ling; Izuddin, Wan Ibrahim; Zulkifli, Idrus; Samsudin, Anjas Asmara; Mustapha, Noordin Mohamed (Elsevier BV, 2021)
The aim of this work was to evaluate the impacts of feeding different levels of postbiotic RI11 on antioxidant enzyme activity, physiological stress indicators, and cytokine and gut barrier gene expression in broilers under heat stress. A total of 252 male broilers Cobb 500 were allocated in cages in environmentally controlled chambers. All the broilers received the same basal diet from 1 to 21 d. On day 22, the broilers were weighed and grouped into 7 treatment groups and exhibited to cyclic high temperature at 36 ± 1°C for 3 h per day until the end of the experiment. From day 22 to 42, broilers were fed with one of the 7 following diets: negative control, basal diet (0.0% RI11) (NC group); positive control, NC diet + 0.02% (w/w) oxytetracycline (OTC group); antioxidant control, NC diet + 0.02% (w/w) ascorbic acid. The other 4 other groups were as follows: NC diet + 0.2% cell-free supernatant (postbiotic RI11) (v/w), NC diet + 0.4% cell-free supernatant (postbiotic RI11) (v/w), NC diet + 0.6% cell-free supernatant (postbiotic RI11) (v/w), and NC diet + 0.8% cell-free supernatant (postbiotic RI11) (v/w). Supplementation of different levels (0.4, 0.6, and 0.8%) of postbiotic RI11 increased plasma glutathione peroxidase, catalase, and glutathione enzyme activity. Postbiotic RI11 groups particularly at levels of 0.4 and 0.6% upregulated the mRNA expression of IL-10 and downregulated the IL-8, tumor necrosis factor alpha, heat shock protein 70, and alpha-1-acid glycoprotein levels compared with the NC and OTC groups. Feeding postbiotic RI11, particularly at the level of 0.6%, upregulated ileum zonula occludens-1 and mucin 2 mRNA expressions. However, no difference was observed in ileum claudin 1, ceruloplasmin, IL-6, IL-2, and interferon expression, but downregulation of occludin expression was observed as compared with the NC group. Supplementation of postbiotic RI11 at different levels quadratically increased plasma glutathione peroxidase, catalase and glutathione, IL-10, mucin 2, and zonula occludens-1 mRNA expression and reduced plasma IL-8, tumor necrosis factor alpha, alpha-1-acid glycoprotein, and heat shock protein 70 mRNA expression. The results suggested that postbiotics produced from Lactiplantibacillus plantarum RI11 especially at the level of 0.6% (v/w) could be used as an alternative to antibiotics and natural sources of antioxidants in poultry feeding.